EKRANISASI NOVEL ANANTA PRAHADI KARYA RISA SARASWATI KE FILM ANANTA SUTRADARA RIZKI BALKI - Dewi, Novi Sisla; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2019)
This research aimed to; (a) describe the reduction of Risa Saraswati's Ananta Prahadi novel story text that is not found in the film director Rizki Balki Ananta, (b) describe the addition of Risa Saraswati's Ananta Prahadi novel story text contained in Ananta Director Rizki Balki's film story, (c) describe the varied changes in the text of Anisa Prahadi's novel by Risa Saraswati, contained in the text of the film Ananta director Rizki. This type of research was a qualitative study using descriptive methods. Analyzing technique used theory of ekranisasi or transformation. The results obtained from this study revealed 79 Ananta Prahadi novels by Rizki Balki, 32 text data stories for Ananta films directed by Rizki Balki. In the process of ekranisasi there are additions, subtractions and changes in variations, (a) the reduction of the novel story text occurs as much as 66 data reduction in plot and background, and 3 data reduction in characterization, (b) the addition of the novel story text contained in the film occurs as much as 22 data addition of plot and background, and 2 additional characterizations of data, (c) Changes vary in the text of the film story based on the novel story text as many as 8 changes in plot and background data, and 2 changes in characterization of characters. This happens because of the creativity of the director when adapting novels and films.Â Keywords: Risa Saraswati, novel to movies, Ananta PrahadiÂ